The divergent TGF-beta ligand Dawdle utilizes an activin pathway to influence axon guidance in Drosophila. - Parker, L.; Ellis, J.E.; Nguyen, M.Q.; Arora, K. (Development, 2006)
Axon guidance is regulated by intrinsic factors and extrinsic cues provided by other neurons, glia and target muscles. Dawdle (Daw), a divergent TGF-beta superfamily ligand expressed in glia and mesoderm, is required for embryonic motoneuron pathfinding in Drosophila. In daw mutants, ISNb and SNa axons fail to extend completely and are unable to innervate their targets. We find that Daw initiates an activin signaling pathway via the receptors Punt and Baboon (Babo) and the signal-transducer Smad2. Furthermore, mutations in these signaling components display similar axon guidance defects. Cell-autonomous disruption of receptor signaling suggests that Babo is required in motoneurons rather than in muscles or glia. Ectopic ligand expression can rescue the daw phenotype, but has no deleterious effects. Our results indicate that Daw functions in a permissive manner to modulate or enable the growth cone response to other restricted guidance cues, and support a novel role for activin signaling in axon guidance.